A Rare Central Venous Catheter Malposition in a 10-Year-Old Girl - Ali Movafegh; Alireza Saliminia; Reza Atef-Yekta; Omid Azimaraghi (Case Reports in Anesthesiology)
Central venous catheters (CVCs) are placed in operating rooms worldwide via different approaches. Like any other medical procedure, CVC placement can cause a variety of complications. We report the case of an unexpected malposition of a catheter in the right internal jugular vein, where it looped back on itself during placement and went upward into the right internal jugular vein. CVC line placement should always be viewed as a procedure that could become complicated, even in the hands of the most experienced operators.